The seed microbiome: Origins, interactions, and impacts - Nelson, Eric B. (Plant and soil, 2018)
Background The development and dispersal of seeds as well as their transition to seedlings represent perhaps the most critical stages of a plant's life cycle. The endophytic and epiphytic microbial interactions that take place in, on, and around seeds during these stages of the plant's life cycle may have profound impacts on plant ecology, health, and productivity. While our understanding of the seed microbiota has lagged far behind that of the rhizosphere and phyllosphere, many advances are now being made. Scope This review explores the microbial associations with seeds through various stages of the plant life cycle, beginning with the earliest stages of seed development on the parent plant and continuing through the development and establishment of seedlings in soil. This review represents a broad synthesis of the ecological and agricultural literature focused on seed-microbe interactions as a means of better understanding how these interactions may ultimately influence plant ecology, health, and productivity in both natural and agricultural systems. Our current understanding of seed-microbe associations will be discussed, with an emphasis on recent findings that specifically highlight the emerging contemporary understanding of how seed-microbe associations may ultimately impact plant health and productivity. Conclusions The diversity and dynamics of seed microbiomes represent the culmination of complex interactions with microbes throughout the plant life cycle. The richness and dynamics of seed microbiomes is revealing exciting new opportunities for research into plant-microbe interactions. Often neglected in plant microbiome studies, the renaissance of inquiry into seed microbiomes is offering exciting new insights into how the diversity and dynamics of the seed microbiome with plant and soil microbiomes as well as the microbiomes of dispersers and pollinators. It is clear that the interactions taking place in and around seeds indeed have significant impacts on plant health and productivity in both agricultural and natural ecosystems.